Tricia Guild, paint box : 45 palettes for choosing color, texture and pattern - Guild, Tricia; Back, Amanda (Quadrille, 2017)
"Renowned for her unique eye for color and her ability to mix paint, pattern and texture to fabulous effect in creating beautiful spaces, Tricia Guild has now, for the first time ever, resolved to lay bare the secrets of her working methods and spell them out simply for us to follow -- not to copy what she does but to learn how to use these skills in our own rooms. Taking inspiration from nature, the cityscape, a different period or culture or from the space itself, Paint Box provides visual inspiration, expert advice, a box of tricks and 45 of Tricia's tried-and-tested palettes."--provided by Amazon.com.